Efek Panjang Serat Terhadap Sifat Tarik Komposit Poliester Berpenguat Serat Buah Lontar Yang Diberi Perlakuan Alkali - Boimau, Kristomus (Universitas Nusantara PGRI Kediri, 2022)
This study aims to observe the impact of the fiber lengths and NaOH treatment on the tensile properties of composite materials made from borassus fiber and polyester matrix. This study used fibers from borassus fruit, Wax Mirror Glass, Polyester and Alkali (NaOH). The NaOH treatment was carried out by soaking the fiber in a 15% NaOH solution for 2 hours. The length of the fiber in this study were short fiber (<1cm) and long fiber (>8 cm). The composition of the number of fibers and matrix in this study was calculated based on the volume fraction of the fiber and the volume fraction of the matrix. The test spesimens were made according to the tensile test standard ASTM D-3039. The results showed that short fiber reinforced composites treated with 15% NaOH for 2 hours had the highest tensile stress value with an average value of 5.896 MPa, while the lowest was found in composites with long fiber reinforcement without alkali treatment with an average value of 1.625 MPa. The results of the macro photo describe the shape of fiber pull out in the composite with long fiber reinforcement without treatment, while the short fiber reinforced composite with alkali treatment has a brittle fracture without fiber pull out.